Literature Review of Learning Media Development using 3D Pageflip in Physics Learning - Andri Yanto Putra; Fatni Mufit (Universitas Islam Negeri (UIN) Mataram, 2022)
Technological progress in the 21st century is progressing very rapidly, one of the fields that has an impact on the development of technology and knowledge is in the field of education. Where the development of technology is increasingly developing interactive multimedia-based media that can assist teachers in delivering material to students and students also more easily understand the material being taught. One of the media development software that has an effective, easy and attractive appearance to use is 3d pageflip. This research is a descriptive study with data analysis techniques using percentages which are then analyzed by descriptive techniques. This research refers to 10 articles that are relevant to the research, namely media development with 3d pageflip. The results of this study are obtained that the average articles developed already have valid criteria, the types of teaching materials that are mostly developed with 3d pageflip are EBooks and the materials developed are different from 10 articles there are 9 different materials developed.